New Challenge in Education: Enhancing Student’s Knowledge through Augmented Reality - Castellanos Sánchez, Almudena; Pérez, Carlota (Augmented Reality: Reflections on Its Contribution to Knowledge Formation, 2023)
The evolution of Augmented Reality has been fast and global, and as it could not be otherwise, its potential in education has begun to be explored. Indeed, we truly believe this technology could be especially valuable in the classroom. First of all, it allows teachers to show virtual objects in the real-world environment which otherwise would be impossible to show. On the other hand, it can also be used to enhance collaborative tasks, as well as encourage socializing and inclusive activities for people with special needs. This chapter gives a brief overview of how the implementation of Augmented Reality can be improved in the school environment not only by showing its versatility and possibilities, but also by describing a number of proposals for applications in different educational levels.
Keywords: augmented reality; didactical methodologies; educational technology; learning; mobile augmented reality; pedagogy; Scopus(2)